Pengaruh Transformasi Digital dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Dinas Energi dan Sumber Daya Mineral Provinsi Kalimantan Timur - Nur Rizki Annisa; Rinda Sandayani Karhab; Vera Anitra (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of digital transformation and work environment on employee performance at the Energy and Mineral Resources Office of East Kalimantan Province. Digital transformation is a crucial element in promoting bureaucratic efficiency and public service quality, while a conducive work environment plays a vital role in enhancing employee motivation and productivity. A quantitative approach was applied using a survey method with a census of 68 employees. The data were analyzed using multiple linear regression with SPSS version 22. The results show that both digital transformation (t = 4.401; sig. = 0.000) and work environment (t = 2.126; sig. = 0.037) have a positive and significant partial effect on employee performance. Simultaneously, the variables also have a significant influence (F = 114.254; sig. = 0.000). The coefficient of determination (R² = 0.780) indicates that 78% of the variation in employee performance is explained by these two factors. These findings emphasize the importance of implementing effective digital systems and creating a supportive work environment to optimize bureaucratic performance in the public sector